2007
DOI: 10.4050/jahs.52.159
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Terrain Impact Tests and Simulations of an Energy Absorbing Fuselage Section

Abstract: Comparisons of the impact performance of a 5 ft diameter crashworthy composite fuselage section were investigated for hard surface, soft soil, and water impacts. The fuselage concept, which was originally designed for impacts onto a hard surface only, consisted of a stiff upper cabin, load bearing floor, and an energy absorbing subfloor. Vertical drop tests were performed at 25 ft/s onto concrete, soft soil, and water. Comparisons of the peak acceleration values, pulse durations, and onset rates were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The sand was represented by an additional 84,672 solid elements that were assigned Mat 5, *MAT_SOIL_AND_FOAM, material property. Information on the characterization of the sand used in this model can be found in Fasanella (2007Fasanella ( , 2008. Like the rigid impact model, the fuselage orientation for sand impact was assumed to be perfectly vertical.…”
Section: Results For Soft Soil (Sand) Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…The sand was represented by an additional 84,672 solid elements that were assigned Mat 5, *MAT_SOIL_AND_FOAM, material property. Information on the characterization of the sand used in this model can be found in Fasanella (2007Fasanella ( , 2008. Like the rigid impact model, the fuselage orientation for sand impact was assumed to be perfectly vertical.…”
Section: Results For Soft Soil (Sand) Impactmentioning
confidence: 99%
“…In fact, helicopter accident data indicate that more than 80% of crashes occur onto multi-terrain surfaces such as water, soft soil, plowed or grassy fields, and shallow swamps, as opposed to smooth prepared surfaces (Baldwin, 2000). In addition, research studies have shown that helicopters, designed for crash resistance onto hard surfaces, do not perform well during multi-terrain impacts (Sareen, 2002;Fasanella, 2007;Witlin, 1997;Tho, 2004;Kohlgruber, 2004;and Pentecote, 2002). For hard and nonyielding impact surfaces, the vehicle's kinetic energy has to be managed by the airframe and internal and/or external energy absorbing devices to ensure load attenuation and adequate post-crash cabin volume.…”
Section: Multi-terrain Impact Testing and Simulationmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to measure its crashworthiness, an aircraft is tested under different situations, including bird strike simulations [2], impact on wings [3], and water ditching and crash landing scenarios on solid grounds [4,5]. These last situations, modeled with a vertical drop test, are commonly employed by structural designers to ensure the desired craft's performance.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens do not collapse after maximum loading is achieved and exhibit a complex unloading response. The composite fuselage section was developed during a three-year research program in the late 1990's and has since been used as a test bed to evaluate structural scaling effects, multi-terrain impacts, seat and occupant loadings, and model correlation studies [22][23][24][25][26][27][28][29][30][31]. A pre-test photograph of the test article is shown in Figure 21 …”
Section: Three-point Bend: Test/analysis Correlationmentioning
confidence: 99%